Partnership between a central agency and its schools: Towards fostering laterality. (July 2018) - Shaari, Imran; Hung, David
Central coordination characterises centralised education systems. Centralised systems pride themselves on efficient systemic planning for strategic foresightedness. This study investigates how educators fostered partnerships towards lateral networking propensities or laterality in a centralised system with hierarchical tendencies. A qualitative method was applied in examining newly formed centrally initiated, yet interest-based partnerships that were supported by central agency affordances. The concept of 'champion resource' – that is, teacher-leaders who champion particular innovations – is introduced to explain the integration of individual resources and collective efforts that can benefit teachers in their learning process through the appropriation of pedagogical innovations. We argue that tenets of partnerships drawn from studies conducted in decentralised systems can inform the dynamics of laterality in centralised systems. In our study, developing laterality starting from champion resource/teacher dyads was witnessed, and the aim is that the dyadic relationships can grow to multi-connected teacher-to-teacher laterality. We argue that the growth of this laterality is both cultivated by the 'champion resource' and afforded through centralised coordination efforts, which we will illustrate through the data from this study. We are in a unique position to study partnerships in a centralised system from the early stages of inception and towards laterality. This study has begun to clarify the possibilities of developing these partnerships systematically, and recommendations are made on how to advance partnerships in centralised systems.